A kind of soft magnetic powder core with high anti-saturation ability and its preparation method and application
Through the double-layer aluminum hydroxide coating structure and annealing heat treatment, the anti-saturation ability of the ferrosilicon aluminum soft magnetic powder core is improved, the problem of insufficient anti-saturation ability in the prior art is solved, and high-frequency stable performance under strong magnetic fields is achieved .
Patent Information
- Application Number
- CN202410485088.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-04-22
AI Technical Summary
The existing iron-silicon aluminum soft magnetic powder core has insufficient anti-saturation capability, which limits its application in large-capacity reactors, especially in strong magnetic fields, with a high permeability attenuation rate.
By preparing a double-layer aluminum hydroxide-coated ferrosilicon aluminum magnetic powder core, aluminum hydroxide is generated by reaction of sodium metaaluminate aqueous solution and ferrosilicon aluminum magnetic powder, and the CO2 gas is introduced to form an outer insulating layer of hexagonal alumina, combined with annealing heat treatment. A dense insulating layer is formed to improve the saturation resistance of the magnetic powder core.
It significantly improves the anti-saturation capability and low eddy current loss of the ferrosilicon aluminum soft magnetic powder core, ensures the frequency stability and high-frequency performance of magnetic permeability, and is suitable for large-capacity reactors.
Smart Images

Figure BDA0004803494490000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a sendust soft magnetic powder core with high anti-saturation capability and a preparation method and application thereof. Background Art
[0002] Metal soft magnetic powder core material is a material made by compounding magnetic powder with insulating medium. In recent years, iron core shunt reactors based on metal soft magnetic powder cores have become a research hotspot in the field of power equipment. They make full use of the natural distributed air gap of magnetic powder core materials, replace the inherent air gap structure of traditional silicon steel cores, significantly reduce the vibration and leakage magnetic flux in the reactor core, and provide a new solution to the problems of local overheating and excessive noise in the reactor. However, in order to keep the magnetic permeability from attenuating under strong magnetic fields and achieve large inductance with fewer winding turns, the material constituting the core column of the iron core shunt reactor needs to have a high anti-saturation ability.
[0003] The magnetic powders of existing metal soft magnetic powder core materials mainly include iron powder, iron silicon, iron nickel, iron nickel molybdenum, iron-based amorphous, iron-based nanocrystalline, etc. Among them, the soft magnetic powder core of sendust (magnetic powder is mainly composed of 4% to 13% Si, 4% to 7% Al and Fe elements) has almost zero magnetostriction coefficient and magnetocrystalline anisotropy, so it has the lowest noise and loss among all kinds of magnetic powder cores, its iron loss is 80% lower than that of iron powder core, and its price is only slightly higher than that of iron powder core. It is the most cost-effective soft magnetic powder core material at present, and it is also the preferred magnetic powder core material for reactor core.
[0004] However, the existing sendust soft magnetic powder core has insufficient anti-saturation capability. The magnetic permeability attenuation rate is about 35% to 80% under a 100Oe DC bias magnetic field, and about 70% to 92% under a 200Oe DC bias magnetic field. It is only suitable for small power occasions, thus limiting the development of magnetic powder core reactors towards large capacity. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of insufficient anti-saturation ability of the sendust soft magnetic powder core in the prior art, thereby providing a sendust soft magnetic powder core with high anti-saturation ability and a preparation method and application thereof.
[0006] To this end, the present invention provides the following technical solutions.
[0007] A method for preparing a sendustine soft magnetic powder core with high anti-saturation capability comprises the following steps:
[0008] Step 1, preparing a sodium aluminate aqueous solution, the mass ratio of sodium aluminate to water is 5: (50-90);
[0009] Step 2, mixing the sodium aluminate aqueous solution and the sendust magnetic powder, heating and reacting to obtain a magnetic powder suspension;
[0010] Step 3, introducing CO2 gas into the magnetic powder suspension, and stopping introducing CO2 gas when the pH value drops to 10-12, continuing to stir the reaction for 60-90 minutes, and drying to obtain double-layer aluminum hydroxide coated magnetic powder;
[0011] Step 4, pressing and molding the double-layer aluminum hydroxide coated magnetic powder;
[0012] Step 5: subjecting the product pressed in step 4 to annealing heat treatment to obtain the Sendust soft magnetic powder core.
[0013] Furthermore, in step 1, the sodium aluminate aqueous solution also includes a crystal form control agent;
[0014] Preferably, the mass ratio of the sodium aluminate to the crystal form control agent is 5:(0.1-0.5);
[0015] Preferably, the crystal form controlling agent includes one or more of sodium pyrophosphate, aluminum sulfate or aluminum fluoride.
[0016] Furthermore, in step 2, the particle size of the Sendust magnetic powder is 14 to 55 μm.
[0017] Furthermore, in step 2, the Sendust magnetic powder comprises, by mass percentage, 7%≤Si≤10%, 2%≤Al<4%, and the remainder is Fe and unavoidable impurities.
[0018] Furthermore, step 2 satisfies at least one of the following conditions:
[0019] (1) The mass ratio of the sodium aluminate aqueous solution to the sendust magnetic powder is (8-12):1;
[0020] (2) The heating reaction is carried out at 60 to 80° C. for 10 to 30 minutes;
[0021] (3) stirring continuously during the heating reaction;
[0022] (4) The Sendust magnetic powder is prepared by an aerosol method.
[0023] Furthermore, step 3 satisfies at least one of the following conditions:
[0024] (1) During the process of introducing CO2 gas into the magnetic powder suspension, the system temperature is maintained at 50-90°C;
[0025] (2) The flow rate of CO2 gas is 180-320 L / h;
[0026] (3) After stopping the introduction of CO2 gas, continue stirring the reaction while maintaining the system temperature at 50-90°C.
[0027] Furthermore, the step 4 comprises: uniformly mixing the double-layer aluminum hydroxide coated magnetic powder with a binder and a lubricant, and pressing and forming the mixture;
[0028] Preferably, the mass ratio of the double-layer aluminum hydroxide coated magnetic powder, the binder, and the lubricant is (50-75): (1-2): 1;
[0029] Preferably, the lubricant comprises polyamide powder and polytetrafluoroethylene powder, and more preferably, the mass ratio of polyamide powder to polytetrafluoroethylene powder is 1:(0.5-1.5);
[0030] Preferably, the binder is a thermosetting resin binder, exemplarily epoxy resin, phenolic resin or silicone resin.
[0031] Furthermore, in step 4, the compression molding comprises:
[0032] Primary pressing: Press for 30s to 150s at 125-148°C and 350-590MPa, then heat to 190-300°C and cure for 45-80min;
[0033] Secondary pressing: Press at 105-124°C and 250-390MPa for 20s-90s, then heat to 180-280°C and cure for 45-80min.
[0034] Furthermore, in step 5, the annealing heat treatment includes:
[0035] In a protective atmosphere, keep the temperature at 150-190℃ for 10-20min; in a protective atmosphere, continue to heat up to 380-490℃, keep the temperature for 45-60min, and cool with the furnace;
[0036] Optionally, the protective atmosphere is argon.
[0037] Optionally, the heating rate of the annealing heat treatment is 3 to 5°C / min.
[0038] In a second aspect, the present invention provides a sendust soft magnetic powder core with high anti-saturation capability produced according to the preparation method.
[0039] Further, the Sendust magnetic powder is coated with an inner insulating layer and an outer insulating layer;
[0040] Preferably, the inner insulating layer is face-centered cubic aluminum oxide, and more preferably, the thickness of the inner insulating layer is 1 to 8 nm;
[0041] Preferably, the outer insulating layer is hexagonal aluminum oxide, and more preferably, the thickness of the outer insulating layer is 120-200 nm.
[0042] In a third aspect, the present invention provides the use of the high anti-saturation ability Sendust soft magnetic powder core in manufacturing an iron core shunt reactor.
[0043] Furthermore, before mixing the sodium metaaluminate aqueous solution and the sendust magnetic powder, the method further includes a step of pre-treating the sendust magnetic powder, that is, repeatedly washing the sendust magnetic powder in anhydrous ethanol for three times and drying the sendust magnetic powder. The purpose of pre-treating the sendust magnetic powder is to prevent the sendust magnetic powder from being oxidized in the air.
[0044] Furthermore, mixing the sodium aluminate aqueous solution and the sendust magnetic powder includes: placing the sodium aluminate aqueous solution and the sendust magnetic powder in a stirring tank and performing ultrasonic dispersion. The purpose of ultrasonic dispersion is to evenly disperse the sendust magnetic powder with a larger dead weight in the sodium aluminate aqueous solution.
[0045] By annealing heat treatment, the double-layer aluminum hydroxide coated on the surface of the magnetic powder obtained in step 4 is decomposed into aluminum oxide, and the double-layer aluminum oxide insulation coating from the inside to the outside of the magnetic powder surface is completed, wherein the inner layer is face-centered cubic aluminum oxide with a thickness of 1 to 8 nm; the outer layer is hexagonal aluminum oxide with a thickness of 120 to 200 nm. The total thickness of the insulating coating layer is controlled to be above 121 nm.
[0046] In order to prevent irregularly shaped magnetic powders from interpenetrating during the subsequent pressing process, which would result in reduced hysteresis and decreased anti-saturation capability, the sendust soft magnetic powder used in the present invention is prepared by an aerosol method.
[0047] The technical solution of the present invention has the following advantages:
[0048] 1. The preparation method of the high anti-saturation ability sendust soft magnetic powder core of the present invention comprises the following steps: step 1, preparing a sodium aluminate aqueous solution, wherein the mass ratio of sodium aluminate to water is 5:(50-90); step 2, mixing the sodium aluminate aqueous solution and sendust magnetic powder, heating for reaction, and obtaining a magnetic powder suspension; step 3, introducing CO2 gas into the magnetic powder suspension, stopping the introduction of CO2 gas when the pH value drops to 10-12, continuing to stir the reaction for 60-90 minutes, and drying to obtain a double-layer aluminum hydroxide coated magnetic powder; step 4, pressing the double-layer aluminum hydroxide coated magnetic powder into a shape; step 5, annealing and heat treating the product pressed in step 4 to obtain the sendust soft magnetic powder core.
[0049] The present invention heats the sodium metaaluminate aqueous solution to cause a catalytic hydrolysis reaction to generate aluminum hydroxide and sodium hydroxide, and the hydroxide ions in the solution react with the aluminum atoms on the surface of the sendust magnetic powder particles to generate an extremely thin layer of aluminum hydroxide in situ on the surface of the sendust magnetic powder. The thin layer of aluminum hydroxide is thermally decomposed by subsequent annealing heat treatment, thereby forming a thin and uniform face-centered cubic aluminum oxide inner insulation layer on the surface of the magnetic powder. The coating obtained in situ is uniform and has good adhesion, which can ensure that the surface of the magnetic powder is completely coated with the insulation layer, avoiding leakage points of the insulation layer, thereby eliminating the uneven insulation layer caused by simple mechanical mixing in the traditional insulation coating process, and ensuring the permeability frequency stability and lower high-frequency loss of the sendust magnetic powder core.
[0050] The present invention introduces CO2 gas into a mixed suspension composed of sendust magnetic powders with inner-layer aluminum hydroxide in-situ coating, so that sodium aluminate undergoes double decomposition reaction to precipitate aluminum hydroxide, which is further coated on the surface of the magnetic powder; the reaction time is controlled to be 60 to 90 minutes so that the thickness of the insulating coating layer meets the use requirements; the PH value of the system is controlled to regulate the crystal structure of the outer aluminum hydroxide layer so that a dense hexagonal aluminum oxide outer insulating layer is formed after annealing heat treatment.
[0051] The outer insulating layer is formed by further hydrolysis of sodium aluminate with the inner insulating layer as the nucleus point, and is completely consistent with the chemical composition of the inner insulating layer, so it can be closely combined with the inner insulating layer. The thickness increases evenly as the hydrolysis reaction continues, and finally forms a thick and uniform coating layer. This double-layer structure ensures the high anti-saturation ability and low eddy current loss of the sendust soft magnetic powder core.
[0052] When the mass ratio of sodium aluminate to deionized water is less than 5:90, the insulating coating finally formed on the surface of the sendust magnetic powder is very thin and the structural demagnetization field is small. Although the soft magnetic powder core has a higher magnetic permeability, it is not enough to obtain sufficient anti-saturation ability. If the mass ratio of sodium aluminate to deionized water exceeds 5:50, the density of the insulating coating of the sendust soft magnetic powder core cannot be guaranteed, and cracks are easily formed after annealing, affecting the comprehensive performance of the powder core.
[0053] 2. The sodium aluminate aqueous solution of the present invention also includes a crystal form controller; preferably, the mass ratio of the sodium aluminate to the crystal form controller is 5:(0.1-0.5). The insulating layer of the present invention is relatively thick. By adding an appropriate amount of crystal form controller to the reaction solution, the interface properties of the subsequent reaction system are continuously changed, and the crystal structure of the outer insulating layer is regulated, so that after annealing heat treatment, a dense and uniform hexagonal alumina outer insulating layer is formed.
[0054] 3. The particle size of the Sendust magnetic powder of the present invention is 14-55 μm, which can increase the pinning point of the magnetic domain wall displacement, thereby further increasing the hysteresis and improving the anti-saturation ability. The smaller particle size also helps to reduce the eddy current loss.
[0055] 4. The sendust magnetic powder of the present invention comprises, by mass percentage, 7%≤Si≤10%, 2%≤Al<4%, and the remainder is Fe and unavoidable impurities.
[0056] The Al content of conventional Sendust powder core is between 4% and 7%. The present invention provides an Al content ratio lower than the conventional one. On the one hand, the alloy composition deviates from the zero magnetocrystalline anisotropy and zero magnetostriction composition range to achieve the purpose of increasing magnetic hysteresis; on the other hand, the Fe content is increased to enhance the saturation magnetic induction intensity of the soft magnetic powder core. The two aspects work together to make the Sendust soft magnetic powder core show a strong anti-saturation ability under a DC bias magnetic field. By controlling the Si content to avoid the precipitation of external phase particles, it is ensured that the magnetic powder matrix has a certain solid solubility and resistivity, and the eddy current loss is reduced.
[0057] 5. When introducing CO2 gas into the magnetic powder suspension, keep the system temperature at 50-90°C and the flow rate of CO2 gas at 180-320L / h. By controlling the system temperature and CO2 gas flow rate, the hydrolysis driving force and coating speed can be controlled to make the coating layer complete and uniform.
[0058] 6. The lubricant of the sendust soft magnetic powder core provided by the present invention includes polyamide powder and polytetrafluoroethylene powder. The lubricant has the functions of lubrication and demolding. The current prior art mainly uses conventional lubricants such as zinc stearate, magnesium stearate, and calcium stearate. However, since conventional lubricants have poor fluidity when heated at high temperatures, the powder will seriously agglomerate after heating above 100°C, which will have an adverse effect on the performance of the finished soft magnetic powder core. The polyamide powder and polytetrafluoroethylene powder composite lubricant used in the present invention has a wider operating temperature range than conventional lubricants and a low friction coefficient. It can overcome the problem of poor fluidity or even agglomeration of the mixed powder when heated at high temperatures, which helps to improve the comprehensive soft magnetic properties of the sendust magnetic powder core and also helps with compression molding.
[0059] More preferably, the mass ratio of the polyamide powder to the polytetrafluoroethylene powder is 1:(0.5-1.5), which is limited within the scope of the present invention to ensure both the demoulding effect of the composite lubricant and the dispersibility of the magnetic powder.
[0060] 7. The compression molding of the present invention includes: primary compression: pressing at 125-148°C and 350-590MPa for 30s-150s, then heating to 190-300°C for curing for 45-80min; secondary compression: pressing at 105-124°C and 250-390MPa for 20s-90s, then heating to 180-280°C for curing for 45-80min.
[0061] The present invention can change the lubrication conditions between powder particles and between powder and mold wall by performing compression molding at a relatively high temperature, making powder particles more prone to rearrangement and plastic deformation. At the same time, a two-step compression and two-step solidification process is used to minimize the molding pressure of each compression while achieving the same powder core density as a single compression. This fundamentally solves the molding difficulty problem of iron silicon magnetic powder due to its room temperature brittleness, effectively reduces the difficulty of compression molding, and a relatively small molding pressure can effectively avoid the internal defects and internal stress problems of the magnetic powder caused by high-pressure compression, effectively reducing iron loss.
[0062] 8. The annealing heat treatment of the present invention comprises: keeping the temperature at 150-190° C. for 10-20 min under a protective atmosphere; continuing to heat up to 380-490° C. under a protective atmosphere, keeping the temperature for 45-60 min, and cooling with the furnace.
[0063] The present invention sets a low temperature platform of 150 to 190°C before the target heat treatment temperature is reached to prevent the temperature surge phenomenon in the furnace. In the prior art, the target heat treatment temperature of the magnetic powder core is usually above 700°C to remove the internal stress of the magnetic powder, thereby reducing the hysteresis loss, but the binder is easy to decompose and volatilize at high temperature, resulting in a decrease in the strength of the magnetic powder core, and the anti-saturation ability of the soft magnetic powder core also decreases with the increase of the heat treatment temperature. Therefore, the present invention improves the fluidity of the coated magnetic powder during the pressing process by increasing the pressing temperature, and controls the internal stress of the powder core within a lower range, so there is no need to select an excessively high heat treatment temperature, thereby avoiding the problem of anti-saturation ability and strength reduction caused by high-temperature heat treatment.
[0064] The present invention adopts high-purity argon as the protective atmosphere to avoid the introduction of harmful impurity elements such as C, N, O and the like which may lead to the deterioration of magnetic properties.
[0065] 9. The double-layer alumina insulation coating of the sendust soft magnetic powder core provided by the present invention is obtained by chemical reaction of sodium aluminate. Compared with the existing phosphoric acid coating and sol-gel technology, the process of magnetic powder insulation coating by sodium aluminate catalytic oxidation combined with double decomposition reaction is relatively simple, the molding and pressing pressure is small, the heat treatment temperature is lower than the conventional one, it can save energy, and it is pollution-free and suitable for large-scale industrial production. DETAILED DESCRIPTION
[0066] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0067] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0068] The silicone resin binder in the examples and comparative examples is the silicone resin powder DC-805 produced by Sinopharm Chemical Reagent Co., Ltd.; the polyamide powder is DuPont PA66 from the United States; and the polytetrafluoroethylene powder is Daikin M112 from Japan.
[0069] Example 1
[0070] This embodiment provides a method for preparing a sendustine soft magnetic powder core with high anti-saturation capability, comprising the following steps:
[0071] (1) Atomized sendust magnetic powder with a particle size of 28 μm was repeatedly rinsed three times in anhydrous ethanol and dried, wherein the sendust magnetic powder had a composition, by mass percentage, of 9.7 wt % Si, 3 wt % Al, and the remainder Fe and unavoidable impurities.
[0072] (2) Sodium aluminate and sodium pyrophosphate are mixed, deionized water is added, and the mixture is stirred evenly to obtain a transparent sodium aluminate aqueous solution containing sodium pyrophosphate, wherein the mass ratio of sodium aluminate, sodium pyrophosphate, and deionized water is 5:0.25:80.
[0073] (3) Add the pretreated Sendust magnetic powder to the transparent sodium aluminate aqueous solution containing sodium pyrophosphate, heat at 75° C., stir and react for 25 minutes to obtain a magnetic powder suspension coated with a single layer of aluminum hydroxide, wherein the mass ratio of the sodium aluminate aqueous solution to the Sendust magnetic powder is 10:1.
[0074] (4) Continuously introduce CO2 gas into the magnetic powder suspension obtained in step (3), monitor the pH value of the system and control the system temperature to 70°C, stop introducing CO2 gas when the pH value drops to 10.5, continue stirring and reacting evenly for 75 minutes, and dry to obtain double-layer aluminum hydroxide coated magnetic powder. The flow rate of the CO2 gas is 260 L / h.
[0075] (5) Mix polyamide powder and polytetrafluoroethylene powder in a ratio of 1:1 to obtain a composite lubricant; mix the double-layer aluminum hydroxide coated magnetic powder obtained in step (4) with the silicone resin binder and the composite lubricant, and press them into shape. The specific process steps include: pressing at a temperature of 125°C, a molding pressure of 480MPa, a pressing treatment time of 60s, and then heating to 260°C for curing for 60min; continue pressing at a temperature of 115°C, a molding pressure of 390MPa, pressing for 60s, and then heating to 200°C for curing for 60min. The mass ratio of the double-layer aluminum hydroxide coated magnetic powder to the silicone resin and the composite lubricant is 65:1.5:1.
[0076] (6) The product of step (5) is subjected to annealing heat treatment in a high-purity argon protective atmosphere, wherein the specific process steps include: heating to 150° C. at a heating rate of 3° C. / min, and keeping the temperature for 15 min; further heating to 420° C. at a heating rate of 3° C. / min, and keeping the temperature for 50 min, and cooling with the furnace to obtain an Sendust soft magnetic powder core.
[0077] Example 2
[0078] This embodiment provides a method for preparing a soft magnetic powder core with high anti-saturation ability, comprising the following steps:
[0079] (1) Atomized iron silicon magnetic powder with a powder particle size of 28 μm was repeatedly washed three times in anhydrous ethanol and dried, wherein the composition of the sendustine magnetic powder, in terms of mass percentage, included: 7.8 wt% Si, 2.5 wt% Al, and the remainder Fe and unavoidable impurities.
[0080] (2) Sodium aluminate and sodium pyrophosphate are mixed, deionized water is added, and the mixture is stirred evenly to obtain a transparent sodium aluminate aqueous solution containing sodium pyrophosphate, wherein the mass ratio of sodium aluminate, sodium pyrophosphate, and deionized water is 5:0.25:70.
[0081] (3) Add the pretreated sendust magnetic powder to the transparent sodium aluminate aqueous solution containing sodium pyrophosphate, heat at 70° C., stir and react for 20 minutes to obtain a magnetic powder suspension coated with a single layer of aluminum hydroxide, wherein the mass ratio of the sodium aluminate aqueous solution to the magnetic powder is 10:1.
[0082] (4) Continuously introduce CO2 gas into the magnetic powder suspension obtained in step (3), monitor the pH value of the system and control the system temperature to 70°C, stop introducing CO2 gas when the pH value drops to 11, continue stirring and reacting evenly for 80 minutes, and dry to obtain double-layer aluminum hydroxide coated magnetic powder. The flow rate of the CO2 gas is 280 L / h.
[0083] (5) Mix polyamide powder and polytetrafluoroethylene powder in a ratio of 1:1 to obtain a composite lubricant; mix the double-layer aluminum hydroxide coated magnetic powder obtained in step (4) with the silicone resin binder and the composite lubricant, and press them into shape. The specific process steps include: pressing at a temperature of 125°C, a molding pressure of 480MPa, a pressing treatment time of 60s, and then heating to 260°C for curing for 60min; continue pressing at a temperature of 115°C, a molding pressure of 390MPa, pressing for 60s, and then heating to 200°C for curing for 60min. The mass ratio of the double-layer aluminum hydroxide coated magnetic powder to the silicone resin and the composite lubricant is 65:1.5:1.
[0084] (6) The product of step (5) is subjected to annealing heat treatment in a high-purity argon protective atmosphere, and the specific process steps include: heating to 150° C. at a heating rate of 5° C. / min, and keeping the temperature for 15 min; further heating to 420° C. at a heating rate of 5° C. / min, keeping the temperature for 50 min, and cooling with the furnace to obtain an iron silicon soft magnetic powder core.
[0085] Example 3
[0086] This embodiment is basically the same as embodiment 1, except that the lubricant in (5) is a conventional zinc stearate lubricant.
[0087] Example 4
[0088] This embodiment provides a method for preparing a sendustine soft magnetic powder core with high anti-saturation capability, comprising the following steps:
[0089] (1) Atomized sendust magnetic powder with a particle size of 28 μm was repeatedly rinsed three times in anhydrous ethanol and dried, wherein the sendust magnetic powder had a composition, by mass percentage, of 9.7 wt % Si, 3 wt % Al, and the remainder Fe and unavoidable impurities.
[0090] (2) Sodium aluminate and sodium pyrophosphate are mixed, deionized water is added, and the mixture is stirred evenly to obtain a transparent sodium aluminate aqueous solution containing sodium pyrophosphate, wherein the mass ratio of sodium aluminate, sodium pyrophosphate, and deionized water is 5:0.25:80.
[0091] (3) Add the pretreated Sendust magnetic powder to the transparent sodium aluminate aqueous solution containing sodium pyrophosphate, heat at 75° C., stir and react for 25 minutes to obtain a magnetic powder suspension coated with a single layer of aluminum hydroxide, wherein the mass ratio of the sodium aluminate aqueous solution to the Sendust magnetic powder is 10:1.
[0092] (4) Continuously introduce CO2 gas into the magnetic powder suspension obtained in step (3), monitor the pH value of the system and control the system temperature to 70°C, stop introducing CO2 gas when the pH value drops to 10.5, continue stirring and reacting evenly for 75 minutes, and dry to obtain double-layer aluminum hydroxide coated magnetic powder. The flow rate of the CO2 gas is 260 L / h.
[0093] (5) Mixing polyamide powder and polytetrafluoroethylene powder in a ratio of 1:1 to obtain a composite lubricant; mixing the double-layer aluminum hydroxide coated magnetic powder obtained in step (4) with an organic silicon resin binder and a composite lubricant to form a composite lubricant, wherein the specific process steps include: pressing at room temperature, a pressing pressure of 1850 MPa, and a pressing time of 60 seconds. The mass ratio of the double-layer aluminum hydroxide coated magnetic powder to the organic silicon resin and the composite lubricant is 65:1.5:1.
[0094] (6) The product of step (5) is subjected to annealing heat treatment in a high-purity argon protective atmosphere. The specific process steps include: heating to 760° C. at a heating rate of 3° C. / min, keeping the temperature for 65 min, and cooling with the furnace to obtain a sendust soft magnetic powder core.
[0095] Example 5
[0096] This embodiment is basically the same as embodiment 1, except that the content of Al in the atomized Sendust magnetic powder in (1) is greater than 4%. The composition of the Sendust magnetic powder is calculated by mass percentage and specifically includes: 9.6wt% Si, 5.4wt% Al, and the remainder is Fe and unavoidable impurities.
[0097] Comparative Example 1
[0098] Atomized iron-silicon-aluminum magnetic powder with a particle size of 28 μm was selected, and its composition was the same as that of Example 1. The magnetic powder was insulated and coated with tetraethyl orthosilicate: ammonia water was slowly dripped into a mixed suspension containing tetraethyl orthosilicate, ethanol, water and atomized iron-silicon-aluminum magnetic powder, and the mixture was stirred continuously. The reaction was continued at 60° C. for 8 hours, and the mixture was stirred until dry to obtain silicon oxide insulated coated magnetic powder. The mass ratio of tetraethyl orthosilicate, ethanol, water and mixed magnetic powder was 1:8:2:1, and the mass ratio of the mixed suspension to ammonia water (10 mol / L) was 600:1.
[0099] Then, the polyamide powder and the polytetrafluoroethylene powder are mixed evenly in a ratio of 1:1 to obtain a composite lubricant; the silicon oxide coated magnetic powder is mixed evenly with the silicone resin binder and the composite lubricant, and pressed into shape. The specific process steps include: pressing at a temperature of 125°C, a molding pressure of 480MPa, a pressing treatment time of 60s, and then heating to 260°C for curing for 60min; continuing to press at a temperature of 115°C, a molding pressure of 390MPa, pressing for 60s, and then heating to 200°C for curing for 60min. The mass ratio of aluminum hydroxide coated magnetic powder to silicone resin and composite lubricant is 65:1.5:1.
[0100] The molded powder core is annealed in a high-purity argon protective atmosphere. The specific process steps include: heating to 150°C at a heating rate of 3°C / min and keeping warm for 15 minutes; continuing to heat to 420°C at a heating rate of 3°C / min and keeping warm for 50 minutes, cooling with the furnace to obtain an Sendust soft magnetic powder core.
[0101] Comparative Example 2
[0102] Aerosolized iron silicon aluminum magnetic powder with a particle size of 28 μm was selected, and its composition was the same as that in embodiment 1. The magnetic powder was insulated and coated by a phosphoric acid passivation coating method: phosphoric acid, deionized water, and aerosolized iron silicon powder were mixed in a mass ratio of 1:10:100, and the powder was heated to above 90°C, stirred evenly, allowed to stand for 3 minutes, solid-liquid separated, and dried to obtain phosphoric acid-coated magnetic powder.
[0103] Then, polyamide powder and polytetrafluoroethylene powder are mixed evenly in a ratio of 1:1 to obtain a composite lubricant; phosphoric acid-coated magnetic powder is mixed evenly with a silicone resin binder and the composite lubricant, and pressed into shape. The specific process steps include: pressing at a temperature of 125°C, a molding pressure of 480MPa, a pressing treatment time of 60s, and then heating to 260°C for curing for 60min; continuing to press at a temperature of 115°C, a molding pressure of 390MPa, pressing for 60s, and then heating to 200°C for curing for 60min. The mass ratio of aluminum hydroxide-coated magnetic powder to silicone resin and composite lubricant is 65:1.5:1.
[0104] The molded powder core is annealed in a high-purity argon protective atmosphere. The specific process steps include: heating to 150°C at a heating rate of 3°C / min and keeping warm for 15 minutes; continuing to heat to 420°C at a heating rate of 3°C / min and keeping warm for 50 minutes, cooling with the furnace to obtain an Sendust soft magnetic powder core.
[0105] Test example
[0106] The properties of the sendust soft magnetic powder cores of Examples 1-5 and Comparative Examples 1 and 2 were tested, and the testing process was as follows:
[0107] Loss Pc at 5kHz / 100mT: The volume loss Pc at a frequency of 5kHz and a magnetic flux density of 100mT is measured using an AC loss test system.
[0108] The magnetic permeability attenuation rate under the DC bias magnetic field is used to characterize the anti-saturation ability of the soft magnetic powder core. The smaller the magnetic permeability attenuation rate, the stronger the material's anti-saturation ability. Magnetic permeability attenuation under the bias magnetic field: The initial inductance L0 of the sample is tested using an LCR digital bridge, and the bias inductance L of the sample is tested using a reactance tester. x The permeability attenuation value under the bias magnetic field is determined by L0 and L x Obtained by calculation.
[0109] Volume resistivity: Use a DC resistance tester to measure the volume resistance value R of the material, and obtain the volume resistivity ρ of the sample by calculation.
[0110] The test results are shown in Table 1.
[0111] Table 1 Properties of soft magnetic powder core
[0112]
[0113] The performance measurement comparison results of Example 1 of the present invention and Comparative Example 1 using the tetraethyl orthosilicate hydrolysis insulation coating process and Comparative Example 2 using the phosphoric acid passivation insulation coating process show that the soft magnetic powder core material provided by the present invention has the advantages of high bulk resistivity and strong anti-saturation ability, and the present invention adopts a high electrical insulation double-layer high temperature resistant alumina insulation coating structure to replace the traditional coating process, thereby achieving uniform, dense and thickened coating layer.
[0114] The performance measurement comparison results of Example 1 of the present invention and Example 3 using conventional zinc stearate lubricant show that the soft magnetic powder core material provided by the present invention has the advantages of high volume resistivity, low loss, and strong anti-saturation ability. The composite lubricant provided by the present invention is used to replace the traditional zinc stearate lubricant to overcome the problem of poor fluidity or even agglomeration of the mixed powder during high-temperature heating, thereby improving the comprehensive performance of the sendust soft magnetic powder core.
[0115] By comparing Example 1 with Example 4, it can be seen that the magnetic powder core material obtained by cold pressing at a high pressure of 1850 MPa and conventionally heat treating at 760°C may cause microcracks in the insulation layer due to the high pressure pressing, increase the loss, reduce the anti-saturation ability, and fail to obtain the optimal magnetic properties.
[0116] By comparing Example 1 with Example 5 using a conventional Al content, it can be seen that the use of the Sendust magnetic powder defined in the present invention can further improve the bulk resistivity and anti-saturation ability of the Sendust soft magnetic core.
[0117] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a high anti-saturation ability Sendust soft magnetic powder core, characterized in that: The following steps are involved: Step 1, preparing a sodium aluminate aqueous solution, the mass ratio of sodium aluminate to water is 5: (50-90); Step 2, mixing a sodium aluminate aqueous solution and sendust magnetic powder, wherein the mass ratio of the sodium aluminate aqueous solution to the sendust magnetic powder is (8-12):1; heating the mixture at 60-80° C. to obtain a magnetic powder suspension comprising sodium aluminate and sendust magnetic powder in situ coated with an inner layer of aluminum hydroxide; Step 3, introducing CO2 gas into the magnetic powder suspension, and stopping introducing CO2 gas when the pH value drops to 10-12, continuing to stir the reaction for 60-90 minutes, and drying to obtain double-layer aluminum hydroxide coated magnetic powder; Step 4, pressing and molding the double-layer aluminum hydroxide coated magnetic powder; Step 5: subjecting the product pressed in step 4 to annealing heat treatment to obtain the Sendust soft magnetic powder core.
2. The method for preparing the high saturation resistance sendust soft magnetic powder core according to claim 1, characterized in that: In the step 1, the sodium aluminate aqueous solution also includes a crystal form control agent.
3. The method for preparing the high saturation resistance sendust soft magnetic powder core according to claim 2, characterized in that: At least one of the following conditions is met: (1) The mass ratio of the sodium aluminate to the crystal form control agent is 5:(0.1-0.5); (2) The crystal form controlling agent includes one or more of sodium pyrophosphate, aluminum sulfate or aluminum fluoride.
4. The method for preparing the high saturation resistance sendust soft magnetic powder core according to claim 1, characterized in that: In the step 2, the particle size of the Sendust magnetic powder is 14 to 55 μm.
5. The method for preparing the high saturation resistance Sendust soft magnetic powder core according to claim 1, characterized in that: In the step 2, the sendust magnetic powder comprises, by mass percentage: 7%≤Si≤10%, 2%≤Al<4%, and the remainder is Fe and unavoidable impurities.
6. The method for preparing a sendust soft magnetic powder core with high saturation resistance according to any one of claims 1 to 5, characterized in that: At least one of the following conditions is met: (1) In step 2, the heating reaction is carried out at 60 to 80° C. for 10 to 30 minutes; (2) In step 2, stirring is continued during the heating reaction; (3) In step 2, the sendust magnetic powder is prepared by an aerosol method; (4) In step 3, during the process of introducing CO2 gas into the magnetic powder suspension, the system temperature is maintained at 50 to 90°C; (5) In step 3, the flow rate of CO2 gas is 180-320 L / h; (6) In step 3, after the CO2 gas is stopped, the system temperature is maintained at 50-90°C during the stirring reaction.
7. The method for preparing a sendust soft magnetic powder core with high saturation resistance according to any one of claims 1 to 5, characterized in that: The step 4 comprises: uniformly mixing the double-layer aluminum hydroxide coated magnetic powder with a binder and a lubricant, and pressing and molding.
8. The method for preparing the high saturation resistance sendust soft magnetic powder core according to claim 7, characterized in that: At least one of the following conditions is met: (1) The mass ratio of the double-layer aluminum hydroxide coated magnetic powder, the binder, and the lubricant is (50-75): (1-2): 1; (2) The lubricant comprises polyamide powder and polytetrafluoroethylene powder, and the mass ratio of the polyamide powder to the polytetrafluoroethylene powder is 1:(0.5-1.5); (3) The adhesive is a thermosetting resin adhesive.
9. The method for preparing a sendust soft magnetic powder core with high saturation resistance according to any one of claims 1 to 5, characterized in that: In step 4, the compression molding comprises: Primary pressing: Press for 30s to 150s at 125-148°C and 350-590MPa, then heat to 190-300°C and cure for 45-80min; Secondary pressing: Press at 105-124°C and 250-390MPa for 20s-90s, then heat to 180-280°C and cure for 45-80min.
10. The method for preparing a sendust soft magnetic powder core with high saturation resistance according to any one of claims 1 to 5, characterized in that: In step 5, the annealing heat treatment includes: Under protective atmosphere, keep warm at 150-190℃ for 10-20min; under protective atmosphere, continue to heat to 380-490℃, keep warm for 45-60min, and cool with the furnace.
11. A Sendust soft magnetic powder core with high anti-saturation capability obtained by the preparation method according to any one of claims 1 to 10.
12. The high saturation resistance Sendust soft magnetic powder core according to claim 11, characterized in that: The Sendust magnetic powder is wrapped with an inner insulating layer and an outer insulating layer.
13. Use of the high anti-saturation ability Sendust soft magnetic powder core according to claim 11 or 12 in manufacturing an iron core shunt reactor.
Citation Information
Patent Citations
Method for preparing magnetically soft composite powder by grinding waste scrap irons
CN102228987A
Double-layer inorganic insulation coated soft magnetic powder and preparation method thereof
CN109979701A